Inherited Wealth over the Path of Development: Sweden, 1810-2010 - Henry Ohlsson; Jesper Roine; Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2014)
Inherited wealth has attracted much attention recently, much due to the research by Thomas Piketty (Piketty, 2011; 2014). The discussion has mainly revolved around a long-run contrast between Europe and the U.S., even though data on explicit historical inheritance flows are only really available for France and to some extent for the U.K. We study the long-run evolution of inherited wealth in Sweden over the past two hundred years. The trends in Sweden are similar to those in France and the U.K: beginning at a high level in the nineteenth century, falling sharply in the interwar era and staying low thereafter, but tending to increase in recent years. The levels, however, differ greatly. The Swedish flows were only half of those in France and the U.K. before 1900 and also much lower after 1980. The main reason for the low levels in the nineteenth century is that the capital-income ratio is much lower than in Old Europe. In fact, the Swedish capital-income ratio was similar to that in the U.S., but the savings and growth rates were much lower in Sweden than in the U.S. Rapid income growth following industrialization and increasing savings rates were also important factors behind the development of the capital-income ratio and the inheritance flow during the twentieth century. The recent differences in inheritance flows have several potential explanations related to the Swedish welfare state and pension system. Sweden was un-European during the nineteenth century because the country was so poor, Sweden is un-European today because so much wealth formation has taken place within the welfare state and the occupational pension systems.
Keywords: D30; J10; N10; 330; Inheritance; Capital accumulation; Inverse mortality multiplier